How farmer characteristics and dimensions of resilience correlate with farmers’ ability to recover from shocks: a case study of Indonesian palm oil smallholders - Hidayat, Nia Kurniawati; Offermans, Astrid; Glasbergen, Pieter (Journal of Agriculture and Environment for International Development (JAEID), 2021)
Most studies on the effects of certification on smallholders’ livelihood emphasize vulnerability while neglecting resilience. This paper assesses the farmer resilience of five different types of palm oil smallholders in Indonesia. We use and apply Speranza’s (2014) framework to assess and understand farmer resilience. We conclude that the correlations between buffer capacity, learning capacity, and resilience are rather weak. Our results further reveal that palm oil smallholders are relatively resilient to price declines, haze from forest fires and El Niño. The differences in resilience between the smallholder groups are small, although certified smallholders collaborating with companies and NGOs seem to be more resilient than uncertified smallholders collaborating with middlemen. The terminated Nucleus Estate Smallholder (NES) system allowed farmers to meet these favourable conditions. A few new initiatives, such as FAIR company-community partnerships may provide similar opportunities for smallholders. We also question the direct link between self-organization and resilience.